Gambaran Visum et Repertum kasus kekerasan terhadap anak di RS. Bhayangkara Manado periode Juli 2015 – Juni 2016 - Ong, Felisia; Mallo, Johannis; Mallo, Nola T. S. (UNIVERSITAS SAM RATULANGI, 2016)
Visum et Repertum is the result of doctor's examination, about what he saw, what the discovery, and what he heard, with regard to the injured person, their health impaired person, and the death of person. Theoretically, child abuse is defined as treatment of physical, mental, or sexual commonly done by those who have responsibility for child welfare. The purpose of this study to describe the results of Visum et Repertum about child abuse in Bhayangkara hospital Manado period July 2015 to June 2016. This type of research is descriptive implemented. Results of the study were obtained from 112 cases the victims are most commonly found in adolescents aged 14 years to 17 years as many as 68 cases. More violence experienced by women as many as 107 cases, in males only occurs as much as 5 cases. Sexual violence experienced by children during a period of 1 year were 100 cases and the total ofÂ physical violence were 12 cases. For a place that is often incident on the incidence of child abuse are Polresta Manado as many as 95 cases. This study proves that the results of Visum et Repertum can be found any physical or sexual abuse in childrenKeywords: Visum et Repertum, child abuse.